Формирование мест современного компактного проживания крымскотатарского населения - Меметова, Р.Ш. (Культура народов Причерноморья, 2013)
Дается анализ современного состояния расселения крымских татар на территории Крыма, изучен процесс возвращения крымских татар с конца 20 века. Рассмотрено современное состояние мест компактного проживания крымскотатарского населения. Ключевые слова: расселение, крымские татары, микрорайон, система расселения, социальная инфраструктура. Надається аналіз сучасного стану розселення кримських татар на території Криму, досліджено процес повернення кримських татар з кінця 20 століття. Розглянуто сучасний стан місць компактного проживання кримськотатарського населення. Ключові слова: розселення, кримські татари, мікрорайон, система розселення, соціальна інфраструктура. In this paper it is gives the analysis of the current state of the resettlement of the Crimean Tatars in Crimea, researched the return process of the Crimean Tatars from the late 20th century and the current state of the places of compact residence of the Crimean Tatar population. Since the 1980’s the Crimean Tatars start unauthorized return to the Crimea. And planned for that time the geography settlement of the Crimean Tatars didn’t match the historical system of resettlement. Currently, in the Crimea was formed about 300 towns and compact residence of repatriatesmicrodistricts. Historical inconsistency of the area of settlement of the Crimean Tatars population in Crimea has led to a disaster processes in forming of the compact residence, to the emergence of unplanned neighborhoods and as a result of the occurrence of many negative socio-economic and environmental problems. Settlements of the Crimean Tatars don’t constitute an integrated system of settlement, and now there is an intensive process of integration of the Crimean Tatars with the pre-existing system of resettlement on the Crimean Peninsula. Key words: resettlement, the Crimean Tatars, microdistricts, the system of resettlement, the social infrastructure.